Influence of Land Use and Land Cover Variations on Soil Carbon Sequestration Potential in the Northern Madhupur Tract, Bangladesh - Farukh, Murad Ahmed; Tasnim, Nishat; Khatun, Rehana; Ali, Aslam; Rahman, Sadiqur (UNIVERSITY OF LAMPUNG, 2025)
This study examines the effects of diverse land use and land cover (LULC) types on soil physico-chemical properties and carbon sequestration potential in the northern Madhupur Tract, Bangladesh. Soil samples were collected from seven LULC types – sal forest, social forest, orchard, bare land, agricultural land, protected area, and built-up area across three depths (0–15 cm, 16–40 cm, and 41–70 cm) between April and September 2022. Key parameters analyzed included texture, bulk density, pH, electrical conductivity (EC), total nitrogen, available phosphorus, exchangeable potassium, available sulfur, organic carbon (OC), and soil organic carbon (SOC). Soil texture ranged from clay loam to clay. Bulk density was the lowest in built-up areas (1.57–1.62 g cm-³) and the highest in protected areas (1.97–2.20 g cm-³). Orchard soils had the highest surface moisture (23.26%). Surface soils showed the highest EC (0.82 dSm-1), total N (0.11%), available P (118.6 ppm), and OC (1.07%), while pH increased with depth, peaking at 6.15. SOC stock differed significantly among land uses (F = 6.56, p < 0.05), highest in social forests (138.67 Mg ha-¹) and built-up areas (134.04 Mg ha-¹). Corresponding CO‚ mitigation potentials were 508.93 Mg C ha-¹ and 491.34 Mg C ha-¹. Agricultural land had the lowest SOC stock (85.31 Mg ha-¹). Enhancing carbon storage through better land management is vital for sustainability and climate resilience.